Strain Sensing Properties of Graphene/Elastic Fabric. Issue 1 (March 2020) - Bustami Shaun, Bayazid; Cai, Runxuan; Sun, Xiaojiang; Huang, Chaokun; Bi, Shuguang; Ran, Jianhua
Abstract: The smart fabric is a new material that began to develop in the 1990s, and on the basis of the nature and function of original material, it joined the features of intelligent perception. On the performance, intelligent fiber can sense the changes of heat, light, chemistry, mechanical, temperature, and electromagnetic, then react accordingly. For smart textiles, the sensor is the core part, now most commonly used micro/nano strain sensor are using silicon and zinc oxide and others inorganic as main material. But inorganic materials have limited deformation ability, once deformation occurs, the sensor will be strictly damaged. So, the development of flexible, high sensitivity, wide range of strain of the flexible intelligent fiber strain sensor has a very important application prospect. For the stretch-able sensor, the prepared conductive material must be placed on the substrate of the flexible polymer. In this paper, graphene is used as conductive material to construct an orderly conductive layer. Waterborne polyurethane was used as dispersant and adhesive, then strengthen the interface between the layer of conductive material and elastic fabric binding force, and finally prepare a kind of high sensitivity, wide strain range, stable performance and high elastic intelligent fibers.